Does Perceived Lack of Control Lead to Conspiracy Theory Beliefs? Findings from an online MTurk sample - Stojanov, Ana; Bering, Jesse M.; Halberstadt, Jamin (PLOS ONE, 2020)
It is widely believed that conspiracy theory beliefs are the product of perceived lack of control. However, to date there is mixed evidence, at best, to support this claim. We consider the reasons why conspiracy theory beliefs do not appear to be based in any straightforward way on control beliefs, interrogating existing findings and presenting new data that call the relationship into question. Across six studies conducted online using MTurk samples, we observed no effect of control manipulations on conspiracy theory beliefs, while replicating previously reported correlational evidence of their association. The results suggest that conspiracy beliefs are not suitable for compensating for threats to control. We discuss possible reasons for the discrepancy between experimental and correlational effects and examine the limitations of the studies.